Danny and the dinosaur go to camp - Hoff, Syd, 1912-2004. (New York, NY : HarperCollins, 1996)
Danny and his friend the dinosaur go to summer camp together.
Keywords: Dinosaurs -- Fiction; Camps -- Fiction